1993
DOI: 10.1063/1.353856
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric polarizabilities of ions in oxides and fluorides

Abstract: A set of 61 ion polarizabilities has been derived from the dielectric constants of 129 oxides and 25 fluorides using a least squares refinement technique in conjunction with the Clausius–Mosotti equation. These polarizabilities can be used to estimate mean dielectric constants of ‘‘well-behaved’’ compounds. They should be particularly useful in calculation of mean dielectric constants of compounds whose dielectric constants have not been determined. They can also be used as a framework for distinguishing unusu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

52
941
3
6

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 2,370 publications
(1,002 citation statements)
references
References 44 publications
52
941
3
6
Order By: Relevance
“…However, the element ratio of spot A (in Table I) showing less oxygen numbers than spot B indicates that the substitution prohibited Ti reduction. 21 7,16,22,23 The e rc decreased with an increasing z value and exhibited similar variation as the average ionic polarizability as shown in Table II before z = 1.5. 7 For z ‡ 1.5, the appearance of Nd 2 (Ti,Mg, Nb) 2 O 7 phase (e r = 36.5) would also contribute to the declination of dielectric constant.…”
Section: Resultssupporting
confidence: 51%
“…However, the element ratio of spot A (in Table I) showing less oxygen numbers than spot B indicates that the substitution prohibited Ti reduction. 21 7,16,22,23 The e rc decreased with an increasing z value and exhibited similar variation as the average ionic polarizability as shown in Table II before z = 1.5. 7 For z ‡ 1.5, the appearance of Nd 2 (Ti,Mg, Nb) 2 O 7 phase (e r = 36.5) would also contribute to the declination of dielectric constant.…”
Section: Resultssupporting
confidence: 51%
“…The trend lines reflect the close similarity in ionic radius between Ba (1.61Å) and K (1.64Å) and Pb (1.49Å) and Sr (1.44Å) in twelve-fold coordination, Table 2. 36,37 Here, we assumed that unfilled sites have the same effective cation radius as the equivalent filled sites due to the rigid octahedral framework. Ubic et al 48 discussed in detail the effective ionic radius of A-site vacancies in perovskite-structured ceramics where the octahedral framework is more compliant.…”
Section: ) Crystal-chemical Frameworkmentioning
confidence: 99%
“…Tin deposition and etching experiments were performed in an apparatus that has been described in detail elsewhere. 11 Tin (Umicore) with a bulk density of 7.3 g/cm 3 and purity of 99.9 % was evaporated from an Effusion Cell EF 40C1 (PREVAC) evaporator operated at 980 • C. The Sn deposition rate was calibrated using a quartz microbalance (INFICON XTM/2 Deposition Monitor). It was found that the evaporation rate as measured using the quartz microbalance (QMB) at 980 • C was approximately 0.4 nm/min.…”
Section: Methodsmentioning
confidence: 99%
“…LaScO 3 have been studied as possible candidates for high-k dielectric applications, due to their possession of a suitably large optical band gap (5-6 eV). Moreover, Sc 2 O 3 has a high dielectric constant (ε = 13) in comparison to SiO 2 (ε = 4.5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation